Value source, value priming, and social norms as predictors of engaging in minor moral/legal violations - Fea, Courtney J. (Kansas State University, 2017)
The current dissertation examined the role value sources and social norms play in people’s likelihood to commit minor moral and/or legal violations. First, using the process of value acquisition as a general guideline, five value sources were hypothesized to influence an individual’s tendency for minor moral/legal crimes. Second, based on social norms theory and social norm interventions, it was hypothesized strategically manipulating social norms may alter a person’s willingness to partake in various immoral and/or illegal activities. Two studies were conducted to test these suppositions. Participants randomly assigned to between-subjects design experiments completed questionnaires via the web. In Experiment 1, participants mindset primed with values from multiple value sources (parental, peer, media, religion, personal) indicated how they “personally would act” if provided the opportunity to commit minor moral/legal violations. Participants primed with personal, parental, and religious values were willing to act as the value source suggested in minor moral/legal violation situations. Participants primed with media values did not necessarily follow the value source’s recommendations regarding minor moral/legal violations. In Experiment 2, participants exposed to low, actual, or high social norm (and severity perception) ratings reported how likely they were to commit the same minor moral/legal violations. Participants shown high norm ratings expressed a greater willingness to engage in minor moral/legal violations than those shown low norm ratings. Results suggested value sources and norm ratings differentially impacted participants’ willingness to be involved in minor immoral and/or unlawful behavior.
Keywords: Social norms; Value source; Values; Moral violations; Legal violations; College students